2015
DOI: 10.1128/aac.00117-15
|View full text |Cite
|
Sign up to set email alerts
|

Mutation atembBCodon 306, a Potential Marker for the Identification of Multidrug Resistance Associated with Ethambutol in Mycobacterium tuberculosis

Abstract: dEthambutol inhibits arabinogalactan and lipoarabinomannan biosynthesis in mycobacteria. The occurrence of mutations in embB codon 306 in ethambutol-susceptible isolates and their absence in resistant isolates has raised questions regarding the utility of this codon as a potential marker for resistance against ethambutol. The characterization of mutations on embB 306 will contribute to a better understanding of the mechanisms of resistance to this drug; therefore, the purpose of this study was to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
6
9
0
Order By: Relevance
“…The results obtained here are in line with earlier findings from Russia, where the presence of embB306 mutations in EMB-susceptible DR isolates was first described, that were confirmed by several following studies (7,8,15,16). The discrepancies between embB306 mutations and EMB resistance in our study were observed only in isolates sensitive to EMB but resistant to at least one of the other first-line drugs, and none of the pan-sensitive isolates carried mutations at embB306.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The results obtained here are in line with earlier findings from Russia, where the presence of embB306 mutations in EMB-susceptible DR isolates was first described, that were confirmed by several following studies (7,8,15,16). The discrepancies between embB306 mutations and EMB resistance in our study were observed only in isolates sensitive to EMB but resistant to at least one of the other first-line drugs, and none of the pan-sensitive isolates carried mutations at embB306.…”
Section: Discussionsupporting
confidence: 82%
“…Prior studies have demonstrated a strong association between embB306 mutations and resistance to INH and RIF or MDR (8,10,11,28). In our study, embB306 mutations were found only in DR isolates, and a strong correlation between these mutations and resistance to INH and RIF and MDR was observed.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Additional mutations were detected in the embB gene (Atg/Gtg, M306V) and pncA gene (cCg/cTg, P62L) that are associated with resistance to ethambutol and pyrazinamide, respectively ( 15 18 ). Furthermore, an A/C substitution was detected at position 514 of the 16S rRNA gene, rrs (MTB000019), and is related to streptomycin resistance ( 19 , 20 ).…”
Section: Genome Announcementmentioning
confidence: 99%